2007
DOI: 10.1016/j.intman.2007.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Intra-regional sales, product diversity, and the performance of merchandising multinationals

Abstract: This study examines the relationship between intra-regional sales, product diversity, and performance of 45 merchandising firms using data from 1997 to 2003. The interaction effects between product diversity and intra-regional sales on performance are explored, using a curvilinear relationship. The analysis integrates three main theories, namely the resource-based view, transaction costs, and organization learning theory. The models measuring a firm's performance by return on assets (ROA) and return on sales (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
4
13
0
Order By: Relevance
“…Performance. We use return on sales (ROS) as the indicator of firm's performance because it is one of the most common metrics to measure the global economic output (Contractor et al, 2003;Delios et al, 2008;Qian et al, 2008;Rugman and Oh, 2010;Ruigrok and Wagner, 2003;Sukpanich and Rugman, 2007;Tallman and Li, 1996) and scale. Independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…Performance. We use return on sales (ROS) as the indicator of firm's performance because it is one of the most common metrics to measure the global economic output (Contractor et al, 2003;Delios et al, 2008;Qian et al, 2008;Rugman and Oh, 2010;Ruigrok and Wagner, 2003;Sukpanich and Rugman, 2007;Tallman and Li, 1996) and scale. Independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…Assaf et al (2012) found a U-shaped relationship for 43 large supermarket chains. Using a regional MNE perspective, Sukpanich and Rugman (2007) and Mohr et al (2014) provided evidence of the performance superiority of home-region orientation for retail firms. Li (2005) found that a home-region strategy provided better performance outcomes for U.S. MNEs in various services industry sectors, but his study excluded retail and food service sectors.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Tallman and Li (1996) developed a theoretical framework that suggested that the similarities of geographic and product diversifications propose potential interaction effects that may impact a firm's performance. Accordingly, several studies have investigated the interactions between geographic and product diversifications (e.g., Tallman and Li, 1996;Hitt et al, 1997;Geringer et al, 2000;Sukpanich and Rugman, 2007;Contractor, 2012, 2014). While the results from these studies are inconsistent, a study by Sukpanich and Rugman (2007), which is closely related to this paper, found that higher levels of home-region sales enhanced the positive impact of product diversity on the performance of large merchandisers.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The logarithm of sales per employee is a widely used measure of OP and is adopted in this study in order to enhance comparability with prior work (Huselid 1995). Based on Sukpanich and Rugman's (2007) approach, we measured MA by the selling and general administrative expenses as a proportion of total sales. In addition, a firm's corporate strategy is inevitably influenced by its PP, and Tobin's Q t−1 is Downloaded by [Simon Fraser University] at 22:40 05 October 2015 used as a proxy of this to control for its potential effects.…”
Section: Control Variablesmentioning
confidence: 99%